2021
DOI: 10.1111/jpc.15839
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of chest computed tomography score with disease severity and laboratory values in children with COVID‐19

Abstract: Aim Although chest computed tomography (CT) score has been well evaluated in adult coronavirus disease (COVID‐19), its use in paediatric cases is insufficiently studied. Our aim is to evaluate the relationship of chest CT score with disease severity and laboratory parameters. Methods Seventy‐six paediatric patients with confirmed COVID‐19 and chest CT evaluation on admission have been included in this study. Chest CT score was calculated for each of the five lobes considering the extent of anatomical involveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Another metaanalysis by Nino et al also reported ground glass opacity as the most common pattern in children, which aligns with our study [38]. Consistent with our study, an abnormal chest CT scan in a study conducted in Istanbul showed a statistically signifcant relationship with the severity of the disease of COVID-19, which was associated with a relative increase in the risk of mortality [39].…”
Section: Dyspnea and Low Oxygen Saturation Raised The Risk Of Death A...supporting
confidence: 92%
“…Another metaanalysis by Nino et al also reported ground glass opacity as the most common pattern in children, which aligns with our study [38]. Consistent with our study, an abnormal chest CT scan in a study conducted in Istanbul showed a statistically signifcant relationship with the severity of the disease of COVID-19, which was associated with a relative increase in the risk of mortality [39].…”
Section: Dyspnea and Low Oxygen Saturation Raised The Risk Of Death A...supporting
confidence: 92%
“…Thus, it has been demonstrated that in children with mild forms of SARS-CoV-2 infection, a higher ultrasound score persists than in children who have not had this infection, unlike children who have had an asymptomatic form, have the same ultrasound score as the children who have not contracted SARS-CoV-2 infection [15]. Some studies report correlations between the tomographic image of the lung in SARS-CoV-2 infection and the elevated alanine aminotransferase, D-dimer and leukocyte values [18].…”
mentioning
confidence: 99%
“…It has been documented that not the entirety of children with COVID-19 has chest CT alterations [5].…”
mentioning
confidence: 99%
“…Moreover, because a significant association between chest CT COVID-19 severity and laboratory results has been observed, CT has been suggested as a tool for assessing the severity of the disease [5].…”
mentioning
confidence: 99%